Optimal use of labor market policies: the role of job search assistance - Conny Wunsch (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper studies the role of job search assistance programs in optimal welfare-to-work programs. The analysis is based on a framework, that allows for endogenous choice of benefit types and levels, wage taxes or subsidies, and activation measures such as monitoring and job search assistance for each period of unemployment in a dynamic environment with negative duration dependence in the exit rates to employment and potential depreciation in reemployment wages. We show that the main role of job search assistance is to delay or prevent situations in which it is no longer optimal to incentivize the worker to provide positive search effort. It is used to restore or maintain some minimum exit rate to employment which increases with the cost-effectiveness of job search assistance. We also find that in line with existing policies, these programs should mainly be used at the beginning of unemployment and for short durations. However, contrary to existing schemes, they should be exclusively targeted at unemployed workers with low initial exit rates to employment. For all other workers, they should only be used if they fail to find a job within reasonable time despite high expected initial exit rates.
Keywords: J64; J65; J68; D82; D86; 330; job search; optimal unemployment insurance; welfare-to-work policies; recursive contracts